The landscape of dementia research in Brazil from 2010 to 2021: a Scopus-based bibliometric study - Ari Alex Ramos; Laiss Bertola; Fabiana Araújo Figueiredo da Mata; Andrew Christopher Claro Miguel; Haliton Alves de Oliveira Junior; Cleusa Pinheiro Ferri (Arquivos de Neuro-Psiquiatria)
Background Several studies have sought to investigate the trajectory of scholarly publications on dementia. Yet, there has been limited attention to contributions from Latin America.